Faktor-Faktor Yang Mempengaruhi Pendapat Juruaudit Sehubungan Dengan Masalah Usaha Berterusan [HF5667. B199 2006 f rb ]. - Hartadi, Bambang (2006)
The objective of the study is to identify whether financial indicator, type of evidence and disclosure will have an influence on the auditors’ going concern opinion. Financial indicator comprise of three levels: strong, moderate and weak. Type of audit evidence comprise of two levels: positive and negative whilst disclosure comprise of two levels: exist or does not exist.